Genetic insights support PARP1 as a mediator in the protective association of ATP-citrate lyase inhibitors with melanoma - Jiawen Lu; Gloria Hoi-Yee Li; Jingyi Hu; Zhenqian Wang (Communications Biology)
Abstract ATP-citrate lyase (ACLY) inhibitors emerge as a promising anti-cancer strategy, yet their causal effects across various cancer types remain unclear. Here, we employ a drug-target Mendelian randomization (MR) approach using four cis-expression quantitative trait loci for blood ACLY gene expression as genetic instruments to mimic ACLY inhibition. We utilize genetic data from the eQTLGen consortium (N = 31,684) for ACLY expression, the deCODE study (N = 35,559) for plasma proteome, and large-scale cancer genome-wide association studies consortia (N from 49,708 to 417,127) to investigate the association of genetically mimicked ACLY inhibitors with 17 cancers and identify potential mediating proteins. Genetically proxied ACLY inhibition is strongly associated with reduced melanoma risk (odds ratio [95% confidence interval (CI)]: 0.85 [0.78, 0.92]) in a combined analysis of two independent outcome datasets. Proteome-wide MR screening 1517 plasma proteins identifies 3 proteins associated with melanoma, with Poly [ADP-ribose] polymerase 1 (PARP1) showing strong colocalization support. Mediation analysis further suggests PARP1 as a mediator in the protective effect of ACLY inhibition on melanoma (mediated proportion [95% CI]: 51.52% [5.45%, 97.58%]). Follow-up and validation analyses support the robustness of these results. This study illuminates the therapeutic potential of ACLY inhibition in melanoma, with PARP1 implicated as a potential mediator, offering avenues for targeted interventions.